Factors Affecting the Control of Chronic Rhinosinusitis With Nasal Polyps: A Comparison in Patients With or Without NERD. (March 2021) - Lilja, Markus Jukka; Koskinen, Anni; Virkkula, Paula; Vento, Seija Inkeri; Myller, Jyri; Hammarén-Malmi, Sari; Laulajainen-Hongisto, Anu; Hytönen, Maija; Mäkitie, Antti; Numminen, Jura; Sillanpää, Saara; Raitiola, Hannu; et al.
Objectives: The aim was to compare the control of chronic rhinosinusitis with nasal polyps (CRSwNP) after endoscopic sinus surgery (ESS), in patients with/without nonsteroidal anti-inflammatory drug exacerbated respiratory disease (NERD). Study Desing : A retrospective hospital-based sample of CRSwNP patients with/without NERD with follow-up. Setting: Tertiary rhinology centers. Methods: Electronic patient record data from 116 CRSwNP patients (46 with NERD and 70 without NERD) undergoing ESS during 2001–17 were studied. Mean follow-up time was 9.9 years (range 1.1–15.3). Endpoints reflecting uncontrolled CRSwNP were revision ESS, and need for rescue/advanced therapy (e.g. antibiotics, oral corticosteroids and/or biological therapy) during follow-up. NERD was variable of interest and gender, age, asthma, allergic rhinitis (AR), smoking, Lund-Mackay (LM) score of sinus computed tomography scans previous ESS and baseline total ethmoidectomy were used as covariates. Results: Twenty-one (49.7%) NERD patients and 18 (25.7%) non-NERD patients underwent revision ESS within a mean ± SD of 4.3 ± 2.8 and 3.7 ± 2.6 years, respectively (p = .013, by Logrank test). In Cox´s regression models, NERD, female gender, young age, asthma, AR, previous ESS, and lack of total ethmoidectomy were associated with revision-ESS. In adjusted model, only the total ethmoidectomy predicted revision-free survival. In adjusted logistic regression model, there was an insignificant trend that NERD and LM score were associated with the need for rescue/advanced therapy in the follow-up. Conclusions: Patients with NERD had higher risk of uncontrolled CRSwNP than patient group without NERD, as measured by revision ESS and/or need for rescue/advanced therapy in the follow-up. In addition, baseline total ethmoidectomy was associated with revision-free survival.